Anti-inflammatory and Antioxidant Properties of Almond-Skin Acetonic Extract in Zebrafish (Danio rerio) Copper-Sulphate-induced Inflammation - Barbosa, Rúben; Martins, Ana; Oliveira, Ivo Vaz; Dias, Maria Inês; Monteiro, Sandra M.; Venâncio, Carlos; Félix, Luís (Planta Medica, 2025)
This study aimed to assess the properties of an acetone-based almond-skin (Prunus dulcis) extract and examine its effects on chemically induced inflammation by evaluating associated oxidative changes in an in vivo model. The phytochemical composition was analysed by LC-MS/MS while the antioxidant capacity was evaluated using DPPH, ABTS, and FRAP assays. The neutrophil migration was assessed using a CuSO4-induced inflammation model in a transgenic zebrafish line (Tg(mpx : GFP)i114). Three days post-fertilisation zebrafish larvae were treated with 5 and 25 µg/mL extract for 1 h and then exposed to 10 µM CuSO4 for 40 min. Following exposure, various biochemical markers were assessed, along with neurobehavioral effects. The polyphenolic profile revealed a high flavonoid content and good antioxidant properties confirmed by the DPPH, ABTS, and FRAP assays. The extract reduced neutrophil migration in a concentration-dependent manner, indicating anti-inflammatory activity. Additionally, it decreased reactive oxygen species (ROS) production and cell death without affecting mitochondrial membrane potential. The extract also mitigated oxidative damage, as shown by reduced malondialdehyde and protein carbonylation levels, alongside decreased antioxidant response markers. Neurobehavioral effects induced by CuSO4 were alleviated, as evidenced by improved touch-evoked responses. These findings suggest that almond-skin extract holds significant antioxidant and anti-inflammatory properties, possibly through modulation of ROS and calcium signalling pathways.
Keywords: antioxidant; anti-inflammatory; zebrafish; copper; almond skin